Quality of Life in Patients With a Major Mental Disorder in Singapore - Choo, Carol C.; Chew, Peter K. H.; Ho, Cyrus S.; Ho, Roger C. (Frontiers in Psychiatry, 2019)
Background: There has been a paradigm shift in mental health service delivery from a focus on reducing symptoms, to a more holistic approach, which considers Quality of Life (QoL). Method: This study aimed to explore prediction of Quality of Life (QoL) in Asian patients with a major mental disorder i.e., depression or schizophrenia in Singapore. In the current study, there were 43 patients (65.1% females) with depression, their ages ranged from 18 to 65 (M = 44.63, SD = 12.22). The data were combined with the data on patients with schizophrenia, there were 43 patients (65.1% females) with schizophrenia, their ages ranged from 18 to 65 (M = 44.60, SD = 12.19). Results: The components of QoL were examined i.e., Physical Component Summary (PCS) and Mental Component Summary (MCS). For all patients, social support and age accounted for 17.3% of the variance in PCS, F(2, 83) = 8.66, p < .001. For patients with depression, disorder severity, age, and duration of treatment accounted for 48.3% of the variance in PCS, F(3, 39) = 12.15, p < .001. For patients with schizophrenia, education (Primary or Lower vs. Post-Secondary or Higher) and emotional coping accounted for 21.3% of the variance in PCS, F(2, 40) = 5.40, p < .01. For all patients, self-efficacy and age accounted for 27.0% of the variance in MCS, F(2, 83) = 15.37, p < .001. For patients with depression, disorder severity accounted for 45.6% of the variance in MCS, F(1, 41) = 34.33, p < .001. For patients with schizophrenia, number of hospitalizations accounted for 18.5% of the variance in MCS, F(1, 41) = 9.29, p < .01. Conclusion: The findings were discussed in regards to implications in interventions to enhance QoL of patients with schizophrenia and depression in Singapore. Keywords: schizophrenia, depression, quality of life, Physical Component Summary, Mental Component Summary